The absorption spectrum of water between 13 540 and 14 070 cm-1: ICLAS detection of weak lines and a complete line list; Journal of Quantitative Spectroscopy and Radiative Transfer; Vol. 133, № 11 - Oudot С.; Regalia S.; Mikhailenko S. N. Semen Nikolaevich; Thomas X.; Decatoire D. (2012, 2012)
Title screen